Protection of the Defendant's Human Rights from a Fiqh Perspective (Ta'zir Study and Analysis of Adultery Perpetrators) - Hasan Munthe; M Zul Fadhlan Rezeki (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
This paper examines the protection of the defendant's human rights from the perspective of Islamic jurisprudence (fiqh jinayah) by emphasizing the concept of ta'zīr and linking it to the analysis of adultery perpetrators. Islamic jurisprudence is not solely oriented towards punishment, but also upholds procedural and substantive justice through the application of the presumption of innocence, strict standards of proof, and the principle of proportionality in imposing sanctions. In adultery cases, Islamic law stipulates very strict evidentiary requirements, such as valid confessions or testimony that meets certain criteria, thus providing protection for the defendant from the possibility of wrongful conviction. This study uses a library research method with a normative-analytical approach to primary and secondary sources, including classical fiqh literature and relevant contemporary scientific works. The results of the study indicate that the concept of ta'zīr provides discretionary space for judges to impose sanctions that are educational, preventive, and proportional, especially when the elements of hudūd are not met in adultery cases. This discretion allows the judge to consider social conditions, the level of guilt, and the interests of the accused, so that Islamic jurisprudence not only functions as an instrument of law enforcement, but also as a means of protecting human dignity in line with the principles of human rights.